EMPLOYING QAR STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Hendri, Jon (Teaching English as a Foreign Language Overseas Journal, 2022)
The objectives of the research was to see how Question Answer Relationship (QAR) strategy assisted students to improve their reading comprehension and describe the situation when Question Answer Relationship (QAR) strategy was employed in the reading class. The researcher was applied pre experimental design. The population was the Second Grade Students of SMPN ciptodadi in 2021/2022 Academic Year. The total number of population is 30 students. The researcher was used purposive sampling technique. relatively baseline knowledge based on their test examination average scores. The total number of sample was 30 students from class. In analyzing the numerical data, the writer was used SPSS for windows.  After implementing the research, the researcher concludes that The use of Question Answer Relationship (QAR) strategy in teaching reading enriches the students’ reading comprehension; it is proved by the mean score of the students’ posttest. The t-test of the students’ reading achievement in posttest was smaller than ? (0.000 < 0.05).  It meant that the H1 of the hypothesis was accepted